The Effect of Financial Performance on share prices with Earnings Per Share as a Moderation Variable - Dyatri Utami Arina Absari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research was aimed to examine the effect of proxied financial performance on stock price by using Earning Per Share as its moderating variable. This research was to used historical data in predicting future stock prices using Financial Performance. The purpose of this study was to determine the effect of financial performance on stock price by using Earning Per Share as a moderating variable. For research sample was using the company listing on the Indonesia Stock Exchange for a period 2017-2019, to obtain a sample of 45 companies for the 3 period (2017-2019). Analysis of the data was used a simple regression analysis. Value, other variables that had no effect on stock price were liquidity, asset size, debt equity ratio (DER), return on equity (ROE). The company's financial performance that effects the stock price is Earning Per Share as a Moderating Variable's.